Effect of nitrogen substituting carbon on high-temperature mechanical properties and wear performance of Cr–Mo–V hot-working die steel - Jinbo Gu; Junwei Yin; Hongxiao Chi; Lihao Li; Jian Zhou; Dangshen Ma (Journal of Materials Research and Technology, 2025)
The effect of nitrogen substituting carbon on the high-temperature mechanical properties and wear performance of Cr–Mo–V hot-working die steel (HWDS) at 500–600 °C was investigated. The results indicate that nitrogen substitution for carbon significantly increased the quantity and stability of undissolved V(C, N), enabling the quenching temperature of the steel to increase from 1030 °C to 1100 °C while obtaining grains of similar size. Nitrogen substitution for carbon could increase both the strength and plasticity of Cr–Mo–V steel at 500 °C, while decreasing the plasticity at 600 °C due to weaker bonding force between the undissolved V-rich carbides and matrix. The influence of nitrogen substituting carbon on high-temperature wear resistance is consistent with its influence on high-temperature plasticity. Nitrogen substitution for carbon intensifies the degree of high-temperature oxidation, improving wear-resistance of HWDS at 500 °C, but reduces the wear resistance at 600 °C. These different effects are mainly attributed to the different roles played by undissolved V-rich carbides at different temperatures.